High‐fidelity Recognition of Organotrifluoroborate Anions (R−BF3−) as Designer Guest Molecules. Issue 60 (31st August 2022) - Sheetz, Edward G.; Zhang, Zhao; Marogil, Alyssa; Che, Minwei; Pink, Maren; Carta, Veronica; Raghavachari, Krishnan; Flood, Amar H.
Abstract: The recognition of boron compounds is well developed as boronic acids but untapped as organotrifluoroborate anions (R−BF3 − ). We are exploring the development of these and other designer anions as anion‐recognition motifs by considering them as substituted versions of the parent inorganic ion. To this end, we demonstrate strong and reliable binding of organic trifluoroborates, R−BF3 −, by cyanostar macrocycles that are size‐complementary to the inorganic BF4 − progenitors. We find that recognition is modulated by the substituent's sterics and that the affinities are retained using the common K + salts of R−BF3 − anions. Abstract : Organic trifluoroborate anions (R−BF3 − ) are found to be competent size‐matched binding partners for cyanostar macrocycles. Binding involves the BF3 − headgroups and is modulated by the sterics of the substituent. Small vinyl and methyl substituents bind equally well and lay a foundation for the guest‐design of self‐assembled architectures.